Study on Meshing Mechanism of Teeth Back and Dynamic Contact- impact of Gear Pair - Wei Wei; Yang Guang; Wang Siyu (Jixie chuandong)
The meshing impact of teeth back which may lead to the phenomenon of low- transmission efficiency,poor accuracy and the decreased stability is studied by considering the teeth backlash,errors and deformation of the gears. Based on the finite element model of dynamic contact of the spur gears,the effects of rotate speed and load on the back meshing is obtained by simulating the meshing characteristic of the gear. The research result shows that both normal meshing and back meshing of gear teeth exist alternately in a certain speed and load condition. The impact of back meshing becomes serious with the increase of the speed of the driving gear. While,it may be weakened with the increase of the load applied on the driven gear within a certain level. When the phenomenon of back meshing happens in the meshing process,the contact force on the normal surface changes between zero and peak magnitude. At the same time,the actual meshing process of gear pairs is a regular cycling changes of normal meshing,mesh apart,back meshing,normal meshing. The study has a certain reference value for designing gear system in the aspects of reducing vibration and noise.